Kaesler: Weber - Kaube: Weber - Bruun, Hans Henrik (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
Book Review of: Dirk Kaesler, Max Weber. Preusse, Denker, Muttersohn München: C. H. Beck 2014 Hardcover, 1007 pp. ISBN 978-3-406-66075-7 Price: € 38 Jürgen Kaube, Max Weber. Ein Leben zwischen den Epochen Berlin: Rowohlt 2014 Hardcover, 496 pp. ISBN: 978-3-87134-575-3 Price: € 26,95